Problems of Teaching the Native Language to Even Children - Sleptsov, Yuri Alekseevich (Этническая культура, 2025)
This paper examines the functioning of the Even language in modern conditions. The research material is based on observations of the process of teaching Even children their native language. Using theoretical analysis and generalization of pedagogical experience, the author investigated and identified the most effective forms and means of teaching the Even language. The study covers northeastern Yakutia, specifically the Momsky (Even) National District. The small Even people, formerly known as Lamuts, live across a significant territory in northeastern Russia. They lead a nomadic lifestyle, constantly moving from one pasture to another, which is required by their traditional form of economy – domestic reindeer herding. Currently, the Even language is endangered; its use is declining, and its transmission to the younger generation is declining. Textbooks do not always meet the objectives of teaching dialects. In this paper, the author, using theoretical analysis and generalization of pedagogical experience, determines the most effective forms and means of teaching Even children. It is important to preserve the cultural context of the language through education, traditions, folklore, and its active use in the socio-cultural environment. Creating conditions for systematic and successful teaching of the native language to Even children should include expanding the scope of language use and its integration into everyday life.